2014
DOI: 10.1101/cshperspect.a020586
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Development and Function in Zebrafish

Abstract: The zebrafish is a premier vertebrate model system that offers many experimental advantages for in vivo imaging and genetic studies. This review provides an overview of glial cell types in the central and peripheral nervous system of zebrafish. We highlight some recent work that exploited the strengths of the zebrafish system to increase the understanding of the role of Gpr126 in Schwann cell myelination and illuminate the mechanisms controlling oligodendrocyte development and myelination. We also summarize si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 202 publications
(266 reference statements)
2
100
0
2
Order By: Relevance
“…In zebrafish, pericytes, located in the vicinity of the basilar artery, begin to migrate along the central arteries originating from the PHBCs at approximately 60 hpf, about 30 hours after the start of angiogenesis/barriergenesis (Ando et al, 2016). In contrast, it remains to be determined when radial glial cells (progenitors to astrocytes) differentiate into cells that interact with BECs (Lyons and Talbot, 2014). Future experiments using transgenic zebrafish that label BECs, pericytes, and astrocytes could reveal the real-time, in vivo interactions of these cells during the formation of the neurovascular unit.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, pericytes, located in the vicinity of the basilar artery, begin to migrate along the central arteries originating from the PHBCs at approximately 60 hpf, about 30 hours after the start of angiogenesis/barriergenesis (Ando et al, 2016). In contrast, it remains to be determined when radial glial cells (progenitors to astrocytes) differentiate into cells that interact with BECs (Lyons and Talbot, 2014). Future experiments using transgenic zebrafish that label BECs, pericytes, and astrocytes could reveal the real-time, in vivo interactions of these cells during the formation of the neurovascular unit.…”
Section: Discussionmentioning
confidence: 99%
“…In the mammalian CNS, this process is characterized by the late prenatal and postnatal emergence and expansion of oligodendrocyte precursor cells (OPCs)(Kessaris et al, 2006; Lu et al, 2002), and their subsequent differentiation into myelinating oligodendrocytes. The developmental origins of these cells have been extensively studied, and we direct interested readers to excellent reviews elsewhere (Bergles and Richardson, 2015; Emery, 2010; Lyons and Talbot, 2015; Nishiyama et al, 2009; Richardson et al, 2006). OPCs persist and proliferate in the CNS well into adulthood (Hughes et al, 2013; Young et al, 2013), an observation that has stimulated study of adult oligodendrogenesis and myelination.…”
Section: Myelination Is a Dynamic Process In The Adult Brainmentioning
confidence: 99%
“…A diverse array of extrinsic factors have been shown to influence the development of the oligodendrocyte lineage and myelination in vivo (Bergles and Richardson, 2015; Lyons and Talbot, 2015; Michalski and Kothary, 2015), indicating that while an innate program of oligodendrocyte differentiation occurs in isolated culture settings, physiologic oligodendrocyte lineage dynamics and myelination are subject to extrinsic regulation. What are the sources of these extrinsic cues?…”
Section: Intrinsic and Extrinsic Myelination Cuesmentioning
confidence: 99%
“…As zebrafish represent the simplest genetically tractable model organism for studying myelination, they have recently garnered much attention from both the glial and broader neuroscience communities (Zalc et al, 2008; Lyons and Talbot, 2015; Stewart et al, 2014). One of the greatest advantages of using the zebrafish model system for studying myelination (or any area of interest) is the ability to perform both forward genetic screens and small-molecule chemical screens on thousands of individuals to define genetic and pharmacological modulators of neurodevelopment (e.g., Driever et al, 1996; Podoga et al, 2006; Kazakova et al, 2006; Rihel et al, 2010; Mathews et al, 2014; Miller et al, 2015; Kokel and Peterson, 2011).…”
Section: Zebrafish and Mouse Advantages And Disadvantagesmentioning
confidence: 99%
“…Zebrafish belong to the jawed-vertebrate lineage and therefore represent a more simple and accessible genetically tractable organism for studying the development of myelinating glial cells. Indeed, within the past ∼10 years, numerous studies have demonstrated that zebrafish can be used to elucidate essential and evolutionary conserved pathways that regulate both SC and OL myelination (Lyons and Talbot, 2015; Preston and Macklin, 2015). In this review, we will summarize similarities and differences between SC and OL development and myelination in zebrafish and mouse, discuss how these differences impact CNS remyelination, and highlight the strengths and weaknesses of each model system for the study of myelinating glia.…”
Section: Introductionmentioning
confidence: 99%